Ab initio study on electronic and optical properties of Cu2NiGeS4 for photovoltaic applications. (1st May 2022) - El Hamdaoui, J.; El-Yadri, M.; Lakaal, K.; Kria, M.; Courel, M.; Ojeda, M.; Pérez, L.M.; Laroze, D.; Feddi, E.
Abstract: In this paper, first principle calculations of Cu2 NiGeS4 (CNGS) are carried out to explore the structural, electronic and optical properties of kesterite compound. Both mBJ+U and HSE potentials are used to calculate the band gap energy. The first approach gives a value of 1.78 eV and the second one a value of 1.76 eV. Our numerical simulation shows that the CNGS exhibits a remarkable high absorption coefficient of the order of 10 4  cm − 1, leading to a promising absorber material for photovoltaic devices. Additional optical properties such as refraction index and dielectric function are also calculated in this work. Furthermore, CNGS-based solar cell simulation was performed through SCAPS software. The calculated values of short-circuit current density J s c, open-circuit voltage V o c, Fill factor FF and power conversion efficiency show that CNGS can be a potential candidate for solar cell application. Highlights: Determination of the structural properties of CNGS kesterite structure. Determination of the electronic and optoelectronic properties of CNGS kesterite structure. Determination of the current–voltage characteristic of CNGS solar cell baseline. Improving the solar cell performance with MoS2 interlayer.